Developing reliable and valid measures for evaluating collaborative governance and adaptability: an example from the Collaborative Forest Landscape Restoration Program - Beeton, Tyler A., author; Teel, Tara L., author; Colavito, Melanie M., author; vonHedemann, Nicolena, author; Huayhuaca, Ch'aska, author; Cheng, Antony S., author; Ghasemi, Benjamin, author; Snitker, Adam J., author; Elsevier Ltd., publisher (Colorado State University. Libraries, 2024)
In recent decades, there has been an increased emphasis on, and application of, collaborative and adaptive forms of environmental governance as a means to address complex social-ecological problems that cannot be achieved alone and support sustainable resource management. However, the majority of research in the collaborative governance and adaptability arena has relied on individual or small-n case studies. This has led to a multitude of definitions, indicators, and indices, which limits our ability to make inferences across cases and contexts. Relatedly, most research lacks formal tests of assumptions related to the dimensional structure and validity of constructs thought to represent collaborative dynamics and adaptability. There is a need for systematic and cross-case assessments situated within robust statistical frameworks to further our understanding of the forces and factors that cultivate collaborative governance and adaptability. We developed and administered a standardized survey assessment, grounded in the theory and practice of collaborative governance and adaptability, to fifteen collaborative projects funded under the Collaborative Forest Landscape Restoration Program (CFLRP) in the United States. We then used confirmatory factor analysis to test the dimensional structure, reliability, and validity of our theoretically and empirically grounded measures. Results indicate the components of collaborative governance and adaptability comprise six dimensions principled engagement, shared motivation, leadership, resources, knowledge and learning, and institutional arrangements. As expected, several dimensions were significantly related, and the pattern of inter-factor relationships aligned with theoretical and empirical assumptions. We also found that the six dimensions represent statistically reliable, valid, and distinct measures that may be used to evaluate collaborative governance and adaptability. While our focus was on the CFLRP, the assessment can be adapted in other collaborative environmental governance contexts and used as a foundation for addressing key research gaps, including relating collaborative environmental governance processes to social-ecological outcomes and collaborative adaptation and resilience through time. This is a critical line of work given the increased emphasis and reliance on long-term collaborative arrangements to achieve sustainability goals.
Keywords: collaborative governance; collaborative forest landscape restoration; program; adaptability; adaptive capacity